EFFECT OF PROBIOTIC AND PREBIOTIC CONSUMPTION ON BLOOD CHOLESTEROL LEVEL IN THE ELDERLY IN POSYANDU MANISJANGAN YOGYAKARTA - Setyaji, Diyan Yunanto; Setyani, Fransisca Anjar Rina (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2021)
Background: With advanced age, an increase in lipid profile is associated with the incidence of cardiovascular disease. Previous studies showed that the administration of probiotic and/or prebiotic are effective in improving lipid profiles. However, other studies have also shown that probiotic and prebiotic had insignificant effects on lipid profiles.Objectives: Determined the effects of probiotic and prebiotic on blood cholesterol level in the elderly.Methods: A total of 64 elderly who did not take cholesterol-lowering drugs enrolled in the quasi-experiment pretest-posttest design and were assigned to three interventions and control groups. The subjects in PRE-group consumed 100 grams of mung bean porridge per day; the subjects in PRO-group consumed 65 ml of fermented milk enriched with Lactobacillus casei Shirota strain per day; the subjects in PREPRO-group consumed 100 grams of mung bean porridge and 65 ml of fermented milk enriched with Lactobacillus casei Shirota strain per day. All intervention groups received treatment for 4 weeks. The control group did not receive any treatment during the study. Before and after treatment, cholesterol data was collected. Paired t-test, ANOVA, Post-hoc LSD were used for statistical analysis.Results There was an increase in cholesterol levels in PRE, PRO, PREPRO-groups (12.93 mg/dL; 48.37 mg/dL; and 7.62 mg/dL). Among the three intervention groups, only the consumption of probiotic was significant for changes in blood cholesterol levels (p 0.023). The administration of various interventions did not have a significant effect on changes in cholesterol levels (p 0.246) when compared to the control group.Conclusion: Prebiotic and probiotic do not lower blood cholesterol level in the elderly in Posyandu Manisjangan Yogyakarta.